Concealed Cathode Degradation in Lithium-Ion Cells with a Ni-Rich Oxide. Issue 4 (1st April 2022) - Rodrigues, Marco-Tulio F.; Gim, Jihyeon; Tornheim, Adam; Kahvecioglu, Ozgenur; Luo, Mei; Prado, Andressa Y. R.; Trask, Stephen E.; Croy, Jason; Abraham, Daniel P.
Abstract : Difficulties with sourcing cobalt and the interest in increasing cell energy have motivated the development of Ni-rich oxide materials for lithium-ion battery cathodes. Despite the intense research on the topic, there is limited information available on the long-term performance of novel cathode formulations. Here, we evaluate the stability of LiNi0.9 Mn0.05 Co0.05 O2 in full-cells tested for over five months, assessing how cycling, voltage and electrolyte additives impact cathode aging. We use differential voltage analysis to extract insights about the cathode from the full-cell data and identify the isolation of cathode particles in the delithiated (charged) state as a relevant mode of aging. Importantly, this particular mechanism of cathode aging does not cause immediate cell capacity fade, causing the simple analysis of cell capacity retention to overestimate the cathode stability under the investigated conditions. Our observations serve as cautionary tale indicating that careful analysis of data from extended testing may be required for assessing the performance of Ni-rich cathodes and for evaluating how these materials are affected by electrolyte additives.